Person-job fit and its relationship with work attitudes: a study of Christian missionaries from Australasia : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Manson, Jennifer Margaret (Massey University, 2007)
Do Christian missionaries who exhibit good person-job fit, (‘aligned’ with host nation colleagues and ‘in harmony’ with expatriate colleagues), experience more positive work attitudes? Personjob fit was conceptualized in terms of competencies. Perspectives on what competencies the role of missionary requires were obtained from 3 groups of subject matter experts: host nation colleagues, missionaries, and mission agency leaders. In Study I, subject matter experts (host nation colleagues, n=22, missionaries, n=25, and agency leaders, n=23) rated the ‘Universal Competency Framework’ (SHL) 20-level competencies. Host nation colleagues differed significantly on 3 of the competencies, suggesting that in this sample, the perspective of expatriates on the role of a missionary was not fully aligned with that of host nation colleagues. In Study 2, a sample of 130 current overseas missionaries self-assessed their performance and provided their own ratings of the importance of the competencies used in Study 1. Measures of Person-Job fit (Demands-Abilities fit, Supplies-Values fit and Perceived Performance) were regressed against outcome variables (job satisfaction, work engagement and satisfaction with life). Results indicated that a person’s fit with the job as described by both host nation colleagues (Alignment) and other expatriates (Harmonization) is positively associated with job satisfaction, work engagement and satisfaction with life. These results offer support for competencies as an effective method of describing missionary roles. Possible implications for enhancing the effectiveness and well-being of missionaries, and other aid and development workers, are discussed.
Keywords: Competency; Expatriates; Job satisfaction; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380104 Personality, abilities and assessment